Variational Iterational Method for Solving Some Real Life Applications - Dunya Mohee Haider; Ali Abdul Kadhum Ruhaima (Journal of Madenat Alelem University College, 2019)
In this work, Variational  Iterational Method  ,which is a modified Lagrange Multiplier, was used to solve a nonlocal problems arising in thermoelastisity , where the one dimensional nonhomogeneous Heat equation was introduced together with the initial condition and the homogenous nonlocal conditions to reach the analytical solution.